THE TPACK CONFIDENCE OF PRE-SERVICE TEACHERS IN SELECTED PHILIPPINE TEACHER EDUCATION INSTITUTIONS - Romell A. Ramos; Edward E. Babasa; Imelda B. Vergara; Bernadeth I. Manalo; Lorna L. Gappi; Tina G. Morfi (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The changing educational landscape of Philippine education in the past decade poses challenges to the implementers of the curriculum innovations – the teachers. Consequently, this has put more pressure on the teacher education institutions (TEIs) to produce a quantity of quality teachers. From this context, this paper examines the technological, pedagogical, and content knowledge (TPACK) confidence level of pre-service teachers in selected Philippine teacher education institutions. The TPACK Model has been a very useful framework for academic stakeholders to understand and measure the level of technology integration in teaching and learning. Using a 64-item self-diagnostic questionnaire designed to measure the dimensions of TPACK in terms of learning experience and practice, and assessing the responses of 187 graduating pre-service teachers from selected Philippine TEIs, the data suggest that the pre-service teachers are fairly confident with the learning experience they get from the TEIs and that by using these experiences they frequently demonstrate the acceptable teacher competency and standards. Furthermore, the levels of TPACK confidence of the secondary and elementary pre-service teachers significantly differ from each other such that the former are more confident with their learning experience and practice. Data also show that there is a significant relationship between the quality of learning experience and the ability of the pre-service teachers to demonstrate the core competencies of TPACK. Hence, teacher education institutions must consider innovating their curriculum through training, subject-focused pedagogical modeling, and subject-specific technologies.